Analysis of the cognitive and functional behavior of female rats in the periestropause after hormone therapy with estrogen - Esperança, Thainá Daguane [UNESP] (2024)
Perimenopause is a critical period, with severe cycle irregularity and lower estrogen secretion altering redox state biomarkers, leading to behavioral changes. The estrogen hormonal therapy (EHT) being commonly used to alleviate climacteric effects. Therefore, the aim of this study was to analyze anxiolytic profile, recognition memory (short and long term), ambulation, redox status, cell synaptic activity in locus coeruleus and hippocampus of Wistar rats in the periestropause after EHT. Forty rats participated in the study; 20 were treated with corn oil (group 21Mo/Veh; corn oil/0.2 mL/sc; 2x/week) and 20 were submitted to EHT (group 21Mo/E2; 17β-estradiol/15 μg/Kg/sc; 2x/week) for 120 days. Open field, elevated plus maze, object recognition (RO), and footprint tests were performed immediately before and at the end of the treatment period. From the decapitated brains, isolated hippocampus were destined for biochemical analysis, in turn, perfused brains were destined for histological analysis. The 21Mo/E2 group had a significantly greater total time in the central region and a significantly greater number of entries into the open arms compared to the 21Mo/Veh group, as in crossing, rearing and grooming behaviors, evidencing an anxiolytic profile. In the RO test, the 21Mo/Veh group decreased long-term memory, and the 21Mo/E2 group maintained the same index as at 17 months of age, in addition to a better balance of the hippocampal redox state, prevention of neuronal cell loss and better gait. Based on the results, it appears that exogenous E2 supplementation during periestropause may help preserve neurological functions and potentially prevent neuropsychological and neurodegenerative disorders.